Politeia : Groote mannen over staat en maatschappij : Van Plato tot Kant - Bierens de Haan, J.D. (Amsterdam : Elsevier, 1943)
Plato ; Aristoteles ; Augustinus ; van Aquino, Thomas ; Alighieri, Dante ; Erasmus ; Macchiavelli ; Morus, Thomas ; Luther, Maarten ; Calvijn, Johannes ; de Groot, Hugo ; Hobbes, Thomas ; de Spinoza, Benedictus ; Locke, John ; Hume, David ; Frederik de Grote ; Montesquieu ; Rousseau, Jean Jacques ; Kant, Immanuel
boek